An event-related potential study of P300 in preschool children with attention deficit hyperactivity disorder - Tao, Mengjiao; Sun, Jing; Liu, Siqi; Zhu, Yike; Ren, Yongying; Liu, Ziqi; Wang, Xiaoyue; Yang, Wenmin; Li, Guannan; Wang, Xin; Zheng, Wei; Zhang, Jianzhao; et al. (Frontiers in Pediatrics, 2024)
Objective: To study the characteristics of event related potential P300 in preschool children with attention deficit hyperactivity disorder (ADHD) aged 4-6 years (4≤age＜6), and to explore the differences in cognitive function compared with healthy children. To explore a new method for the study of cognitive function in preschool children with ADHD. Methods: A total of 73 preschool children aged 4-6 years were selected from the outpatient clinic of Neurology Department, the ADHD-specialized Clinic and Health Care Department of the Children's Hospital Affiliated to the Capital Institute of Pediatrics from March 2021 to May 2024. They were divided into the ADHD group (45 cases) and healthy children group (28 cases). Event related potential P300 was measured in all children and the amplitude and latency of the wave were compared between the two groups separately. Results: The latency of P300 at all the recording electrodes (Fz, Cz, Pz, Oz, C3, C4) in the ADHD group was significantly longer than controls (p˂0.05). The wave amplitudes of children with ADHD were significantly higher than controls at Pz and Oz points. Conclusion: The differences between two groups in P300 test show that preschool children with ADHD present longer latency at central line of the brain and bilateral central lobes compared with healthy children, and higher amplitude at the central parietal lobe and central occipital lobe. It may suggest that attention cognition has already impaired in preschool children with ADHD.